2014
DOI: 10.1021/nl5018404
|View full text |Cite
|
Sign up to set email alerts
|

Direct Interrogation of DNA Content Distribution in Nanoparticles by a Novel Microfluidics-Based Single-Particle Analysis

Abstract: Nonviral gene delivery holds great promise not just as a safer alternative to viral vectors in traditional gene therapy applications, but also for regenerative medicine, induction of pluripotency in somatic cells, and RNA interference for gene silencing. Although it continues to be an active area of research, there remain many challenges to the rational design of vectors. Among these, the inability to characterize the composition of nanoparticles and its distribution has made it difficult to probe the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 41 publications
(91 reference statements)
1
39
0
Order By: Relevance
“…We developed a new assay to evaluate plasmid‐containing polyplex nanoparticles utilizing new NTA hardware and software on the NS500 with the capability of discerning fluorescent nanoparticles that contain plasmid DNA from non‐fluorescent nanoparticles. The estimated number of plasmids per PBAE nanoparticle from this method agrees with those published for bPEI nanoparticles analyzed by single particle microfluidic analysis when scaled by particle volume, providing validation for our method . While NTA does require dilution of the sample for analysis, we hypothesize that the characteristics of the particles analyzed following dilution accurately represent the characteristics of the nanoparticles as they would exist following effective dilution for in vitro or in vivo use.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We developed a new assay to evaluate plasmid‐containing polyplex nanoparticles utilizing new NTA hardware and software on the NS500 with the capability of discerning fluorescent nanoparticles that contain plasmid DNA from non‐fluorescent nanoparticles. The estimated number of plasmids per PBAE nanoparticle from this method agrees with those published for bPEI nanoparticles analyzed by single particle microfluidic analysis when scaled by particle volume, providing validation for our method . While NTA does require dilution of the sample for analysis, we hypothesize that the characteristics of the particles analyzed following dilution accurately represent the characteristics of the nanoparticles as they would exist following effective dilution for in vitro or in vivo use.…”
Section: Discussionsupporting
confidence: 77%
“…The estimated number of plasmids per PBAE nanoparticle from this method agrees with those published for bPEI nanoparticles analyzed by single particle microfluidic analysis when scaled by particle volume, providing validation for our method. 54 While NTA does require dilution of the sample for analysis, we hypothesize that the characteristics of the particles analyzed following dilution accurately represent the characteristics of the nanoparticles as they would exist following effective dilution for in vitro or in vivo use. In contrast to methods such as TEM 55 that have previously been used to estimate the number of plasmids contained in a nanoparticle, relatively little perturbation of the particles occurs with our methods utilizing NTA.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is true that the fluorescent labeling method does prevent expression from labeled plasmids, this reduction in reporter gene expression was due to UV exposure that likely results in nicks in the DNA during the labeling process ( Figure S2) and not necessarily fluorophore covalent conjugation. Recent studies have shown that bPEI polyplexes have on the order of 10 plasmids per nanoparticle, 37 meaning that with 20% pH nanosensor DNA used to form polyplexes in uptake and expression experiments, each polyplex would statistically contain unmodified plasmids.…”
Section: Nucleic Acid Ph Nanosensor Synthesis and Validationmentioning
confidence: 99%
“…205 , copyright 2014), and x-dimension through microfabricated cross-section constriction (figure reproduced from ref. 206 ).…”
Section: Figurementioning
confidence: 99%